PUBLIC PARTICIPATION ON OPEN SPACES’ INSPECTION - Azrar Hadi (http://arl.faperta.ipb.ac.id/, 2011)
Scientists agree that open space’s figures and width area in the cities are not only important to the beauty of the city, but also for improving the urban quality of living. It is related to the needs of places for sports and recreational purposes. Open spaces with particular greeneries will also able to fix the decreasing amount of carbon dioxide and other greenhouse gases effect.One cause of the problem is the competition between the need of green open spaces versus the need of commercial land. Knowingly or not, in addition to commercial and other needs, societies in general and especially planners are less persistent in fighting for the presence of green open space. In particular, to show concerns with the proposed protest on its presence, even so aware of any changes in land use than originallyplanned for the green to any other use.Architecture and landscape architecture education ought to play the main role, encouraging its students to understand the importance of green open space provision and further, producing environmentally concerned and well-educated graduates.This paper aims to review with a different perspective, the availability’s indicators of open space in the city, in terms of urban land use management, especially on increasing public awareness through participation in the monitoring changes in use and incompatibilities of the land use according to the plan. The study results shows that the participation of educated people as a watch-dog agents of the land use planning implementations could be the best and effective instruments to address socio-economic and urban architectural issues, instead of relying on local government building inspectors.